SOME PHYSICAL AND CHEMICAL CHARACTERISTICS OF POLYSACCHARIDES OF GROSSULARIA RECLINATA (L) MILL. BERRIES - T. G. Kabirova; S. L. Adzhiakhmetova; L. P. Mykots; E. T. Oganesyan (Фармация и фармакология (Пятигорск), 2015)
During this study we have determined some physical and chemical characteristics of polysaccharides which are: molecular weight, Huggins constant, swelling index. The results showed that the average molecular weight of the objects under study lies from 5246 to 10071. All WSPS had swelling degree raised with the increase of molar mass while the Huggins constant decreased. The minimum value of Huggins constant were noted in berries of Grossularia reclinata which gives evidence of a good interaction of object with water which is coincide with swelling degree.